CFD Modelling of Multiphase Flow through T Junction. (2016) - Athulya, A.S.; Miji Cherian, R.
Abstract: Multiphase flow is a common phenomenon in many industrial process and energy related industries. Pipelines are widely used in industrial applications for the transport of multiphase mixtures of liquid phases or gas and liquid phases. T junction is an important component of pipeline systems. The numerical study of multiphase flow through T junction have been started a long back. This paper presents a model of multiphase flow through T junction and the redistribution phenomenon of phases at the junction using ANSYS FLUENT Software